Perilaku Mendengarkan Radio pada Dewasa Muda Ditinjau dari Kelompok Pengambilan Keputusan (Kasus Radio XYZ) - Endro Puspo Wiroko (Jurnal Ilmiah Psikologi MIND SET, 2017)
This consumer behavior research aimed to identified the decision making to listen to radio among young adults. Focused group discussion and in-depth interview were done to create questionnaire about decision making to listen to radio. Questionnaires were completed by 443 respondents with the criteria of male and female, 24-35 years old, and listen to radio minimum 1 hour per day. Data were analyzed with cluster analysis and crosstab. Result showed that group of young adults as radio listener which potential to be targeted were the entertainment seeker group. Based on the fact, the radio management may look at characteristics of entertainment seeker group in order to develop suitable radio program format and form of promotion that suits the character of young adults as their target.